Predictors of Turnover Intention Among Employees in Nigeria’s Oil Industry - Oluwafemi, Olaoluwa J. (Organizations and Markets in Emerging Economies, 2013)
It has been debated in literature whether context more than disposition predicts organizational outcomes, but the extent to which they predict employee turnover intention has been evaded, whereas beyond theorising, this may have important consequences for employee retention and performance strategy. The predictive roles of contextual (distributive, procedural and interactional justice) and dispositional variables (conscientiousness, agreeableness and emotional stability) on turnover intention among employees in Nigeria’s oil industry were examined. Using cross-sectional survey design and multistage sampling techniques (n =750) employees comprising 534 (71.2%) males and 216 (28.8%) females with a mean age of 35 years and standard deviation of 6.88 participated in the study. The sampling frame in all 12 out of 32 companies from four clusters that make up Nigeria’s oil industry was formed using quota, proportionate and simple random sampling techniques. Data was collected using validated measures of the study variables combined into a single survey questionnaire. Significant negative relationship was found between contextual variables and turnover intention, and between dispositional variables and turnover intention respectively. Controlling for age and tenure, contextual variables accounted for higher variance in turnover intention (R2 = 0.098; F (5, 745) = 22.23, p < .001) ) than dispositional variables (R2 = 0.10; F (8, 742) = 1.51. p < .001, justifying the assumption of weak effects of dispositional traits in strong situations. Managerial implications of the findings are discussed.
Keywords: turnover intention; organizational justice; context; disposition; interaction